Disordering fantasies of coal and technology: Carbon capture and storage in Australia. (December 2016) - Marshall, Jonathan Paul
Abstract: One of the main ways that continued use of coal is justified, and compensated for, is through fantasies of technology. This paper explores the politics of 'Carbon Capture and Storage' (CCS) technologies in Australia. These technologies involve capturing CO2 emissions, usually to store them 'safely' underground in a process called 'geo-sequestration'. In Australia the idea of 'clean coal' has been heavily promoted, and is a major part of CO2 emissions reduction plans, despite the technological difficulties, the lack of large scale working prototypes, the lack of coal company investment in such research, and the current difficulties in detecting leaks. This paper investigates the ways that the politics of 'clean coal' have functioned as psycho-social defence mechanisms, to prolong coal usage, assuage political discomfort and anxiety, and increase the systemic disturbance produced by coal power. Highlights: Clean coal and geological sequestration is part of Australian climate policy. Governments have offered much to carbon capture and storage (CCS) projects. Coal, and coal power, industries have been relatively uninterested. Progress with CCS is problematic and has not lived up to expectations. CCS defends against tackling the connection between coal and climate.